Joint Optimization of RCC Gravity Dam on Complex Foundation Considering Seismic Dynamic Response - LI Jinyou; HU Jiang; GU Zhenhua (Renmin Zhujiang)
To explore the influence of transverse seam cutting of a high RCC gravity dam on the seismic performance of the dam body,this paper takes the RCC gravity dam project of Mahl Hydropower Station in Pakistan with high seismic intensity and sand-mudstone interbedded foundation as the research object.Through the establishment of three-dimensional integral finite element model,the self-compiled viscoelastic dynamic boundary program is introduced.The dynamic response and difference of the dam body under the design earthquake and maximum credible earthquake (MCE) conditions are calculated respectively when the code wave,site wave,and Koyna wave are input.Based on the ratio defined by the design formula of bearing capacity limit state,the seismic safety state of the RCC gravity dam is comprehensively evaluated by simulating the three comparison schemes of 1/3 height,2/3 height,and full joint cutting of transverse seam.The results show that when the code wave is input,under the action of MCE,the resistance effect ratio coefficient η of the dam foundation surface under the 1/3 and 2/3 height schemes of transverse seam cutting is greater than 1.Under the full joint scheme,ηmin=0.91,and the values of η are less than 1 for a total of 6 times within 0.6 s.After comprehensive consideration,the 2/3 height of transverse seam cutting can be used as the construction recommendation scheme.The research results can provide a reference for the optimal layout of the RCC gravity dam project in the conditions of high seismic intensity and complex geology.